IMPLEMENTATION OF THE CONTEXTUAL TEACHING AND LEARNING MODEL IN TEACHING THE ANALYSIS OF ANECDOTAL TEXTS TO STUDENTS OF GRADE X AT SMK NEGERI 1 JATIBARAN IN THE ACADEMIC YEAR 2022/2023 - Nopita, Diana; Hasanudin, Ade; Mustamil, Mustamil (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
The primary motivation for this study was the inadequate ability of students at SMK Negeri 1 Jatibarang Indramayu to analyze anecdotal texts and the challenges faced by teachers in developing effective learning models. The objectives of the research were to assess the effectiveness of the Contextual Teaching and Learning (CTL) model in teaching Grade X students how to analyze anecdotal texts and to outline the learning process. The study employed an experimental approach with a nonequivalent control group design. The research population consisted of all Grade X students, with Grade X AKL 1 (20 students) as the control group and Grade X AKL 2 (20 students) as the experimental group, selected through purposive sampling. Data collection involved written tests and observations. The t-test results revealed a t-value of 4.727, surpassing the t-table value of 2.024, indicating the acceptance of Ha and the rejection of Ho. This suggests that the Contextual Teaching and Learning model is effective in teaching the analysis of anecdotal texts. Therefore, it can be concluded that the Contextual Teaching and Learning model is successfully implemented in teaching Grade X students at SMK Negeri 1 Jatibarang during the 2022/2023 academic year. The analysis of observation data further demonstrates that the application of the Contextual Teaching and Learning model enhances student engagement in the process of analyzing anecdotal texts for Grade X students at SMK Negeri 1 Jatibarang Indramayu in the 2022/2023 academic year.